The Book of Ruth as intra-biblical critique on the Deuteronomic law - Georg Braulik (Acta Theologica)
The Book of Ruth, written in the post-exilic period, constitutes a 'homily on Dt 23-25', (Michael D Goulder). It is the only biblical example of an entire book systematically subjecting a body of laws from the Deuteronomic code to a socio-critical (Rt 1-2) and sexual-critical (Rt 3-4) relecture through various kinds of allusions. The historical prejudice of the 'community law' against the Moabites, refusing them admission to the 'assembly of Yahweh' (Dt 23:4-7), is disproved (throughout the whole book, especially in Rt1), by a counter-story aimed at promoting sympathy (against Neh 13:1-3). Through the reinterpretation of the prohibition sympathy (against Neh 13:1-3). Through the reinterpretation of the prohibition of incest, the brother-in-law marriage is defended against all suspicious (Rt 3). At the same time, it corrects the accusation of incest, which also lingers about the image of the Moabites (Gn 19:30-38). On the other hand, the narrative about the execution of the right to gleaning (Rt2) and the right to the Levirate marriage (Rt 4) intensifies the demands of the Deuteronomic code (Dt 24:19 or 25:5-10). The Ruth novelette turns the Law of Deuteronomy into 'narrative ethics' (Reinhold Bohlen). The driving force for its meta-legal stance and critique, but also for its objective, lies in the portrayel of the 'loving-kindness, love' (chesed) of Yahweh and in calling forth the 'loving-kindness' of his people through the narrated praxis of the stranger Ruth.